Boron nitride aggregate powder, heat sink, and semiconductor device

By using boron nitride aggregation powder with a specific range of tap density and particle gap volume, the problem of poor thermal conductivity and voltage resistance in the existing h-BN particles in the heat sink is solved, and a heat sink with excellent thermal conductivity and good voltage resistance is achieved, which is suitable for high-density electrical and electronic equipment.

CN119841284APending Publication Date: 2025-04-18MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411982587.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-02-27
Filing Date
2020-02-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing boron nitride (h-BN) particles have low thermal conductivity in the heat sink and insufficient voltage resistance, making it difficult to meet the heat dissipation needs of high-density electrical and electronic equipment.

Method used

By preparing boron nitride aggregation powder with a tap density of 0.6 g/ml or more and less than 0.8 g/ml and a particle gap volume of 0.5 ml/g or more, it is used to produce a heat sink with excellent thermal conductivity and good voltage resistance.

Benefits of technology

It is realized that the withstand voltage characteristics of the heat sink are improved without reducing thermal conductivity, and is suitable for high-power and high-density semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221864220000171
    Figure BDA0005221864220000171
  • Figure BDA0005221864220000181
    Figure BDA0005221864220000181
  • Figure BDA0005221864220000182
    Figure BDA0005221864220000182
Patent Text Reader

Abstract

The invention relates to a boron nitride aggregate powder, a heat sink, and a semiconductor device. Provided is a boron nitride aggregate powder having a tap density of 0.6 g / ml or more but less than 0.8 g / ml and a particle interstitial volume of 0.5 ml / g or more. Also provided is a heat sink comprising the boron nitride aggregated powder. The present invention provides a boron nitride aggregated powder which can improve the thermal conductivity of a heat dissipation sheet and has good withstand voltage characteristics, a heat dissipation sheet containing the boron nitride aggregated powder, and a semiconductor device using the heat dissipation sheet.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of February 21, 2020, application number 202080013457.X, and invention name “Boron nitride aggregated powder, heat sink and semiconductor device”. Technical Field

[0002] The present invention relates to a boron nitride aggregated powder which is suitably used for a heat sink for a semiconductor device, a heat sink including the boron nitride aggregated powder, and a semiconductor device using the heat sink. Background Art

[0003] Boron nitride (BN) is an insulating ceramic, and various crystal forms are known, such as c-BN having a diamond structure, h-BN having a graphite structure, and α-BN and β-BN having a disordered layer structure.

[0004] Among these, h-BN has the same layered structure as graphite, is relatively easy to synthesize, and has excellent thermal conductivity, solid lubricity, chemical stability, and heat resistance. Therefore, it is widely used in the field of electrical / electronic materials.

[0005] In recent years, heat dissipation has become a major problem, especially in the electrical and electronic fields, as integrated circuits become more densely packed. Dissipation has become an urgent issue. h-BN is insulating, but it has a high thermal conductivity and has attracted attention as a thermally conductive filler for heat dissipation components.

[0006] However, h-BN is a plate-like particle shape, and although it shows high thermal conductivity in the plate surface direction (ab plane or (002) plane) (usually about 400 W / m·K in thermal conductivity), it only shows low thermal conductivity in the plate thickness direction (C-axis direction) (usually about 2 to 3 W / m·K in thermal conductivity). Therefore, when h-BN is compounded into a resin to prepare a resin composition containing BN particles, for example, when it is desired to mold a plate-like sheet-like molded body, the plate-like h-BN is oriented along the flow direction of the resin composition containing BN particles during molding, that is, the plate surface direction of the sheet-like molded body, and the obtained sheet-like molded body has excellent thermal conductivity in the plate surface direction, but only shows low thermal conductivity in the thickness direction.

[0007] In order to improve the anisotropy of thermal conductivity of h-BN particles, studies have been conducted on aggregated particles in which h-BN particles are less oriented as described above and have shapes other than flaky plates even when filled in a resin.

[0008] Patent Document 1 describes BN aggregate particles having a purity of 93% and a porosity of 50% by volume or less. Patent Document 1 does not describe the tap density, and the thermal conductivity and withstand voltage are insufficient when used in a heat sink for a semiconductor device.

[0009] Patent Document 2 describes BN aggregate particles having a porosity of 50 to 70% by volume and a compressive strength of 1.0 to 4.0 MPa. Patent Document 2 does not describe the tap density, and the thermal conductivity and withstand voltage when used as a heat sink for a semiconductor device are insufficient.

[0010] Patent Document 3 describes an aggregate particle size (D 50 ) is 2 to 200 μm and has a tap density of 0.5 to 1.0 g / ml. Patent Document 3 does not describe the interparticle volume affected by the orientation of primary particles constituting the aggregated particles or the shape of the aggregated particles, and the thermal conductivity and the withstand voltage in the relative evaluation when used for the heat sink of a semiconductor device are insufficient.

[0011] Patent Document 1: International Publication No. 2012 / 070289

[0012] Patent Document 2: Japanese Patent Application Publication No. 2017-82091

[0013] Patent Document 3: Japanese Patent Application Publication No. 2011-98882 Summary of the invention

[0014] An object of the present invention is to provide a boron nitride aggregated powder which can improve the thermal conductivity of a heat sink and has excellent withstand voltage characteristics, a heat sink including the boron nitride aggregated powder, and a semiconductor device using the heat sink.

[0015] Solutions for solving problems

[0016] The present inventors have found that, when boron nitride aggregate powder having a tap density and a particle gap volume within a specific range is used for a heat sink, high thermal conductivity and withstand voltage characteristics can be achieved.

[0017] That is, the gist of the present invention is as follows.

[0018] [1] A boron nitride aggregate powder having a tap density of 0.6 g / ml or more and less than 0.8 g / ml and a particle interstitial volume of 0.5 ml / g or more.

[0019] [2] The boron nitride aggregated powder according to [1], wherein the interstitial volume of the particles is 0.9 g / ml or less.

[0020] [3] The boron nitride aggregated powder according to [1] or [2], wherein the average particle size of the boron nitride aggregated powder is 20 μm or more and 200 μm or less.

[0021] [4] The boron nitride aggregated powder according to any one of [1] to [3], wherein the intra-particle porosity of the BN aggregated particles contained in the boron nitride aggregated powder is 40% or more and 60% or less.

[0022] [5] The boron nitride aggregate powder according to any one of [1] to [4], wherein the boron nitride aggregate powder has a card-house structure.

[0023] [6] A heat sink comprising the boron nitride aggregate powder according to any one of [1] to [5].

[0024] [7] A semiconductor device using the heat sink described in [6].

[0025] Effects of the Invention

[0026] According to the boron nitride aggregated powder of the present invention, a heat sink having excellent thermal conductivity and excellent withstand voltage characteristics can be provided. Using the heat sink containing the boron nitride aggregated powder of the present invention can realize a power semiconductor module having good heat dissipation performance, high quality, excellent thermal conductivity, and high reliability. DETAILED DESCRIPTION

[0027] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with various modifications within the scope of the gist thereof.

[0028] [Boron nitride aggregate powder]

[0029] The boron nitride aggregate powder of the present invention (hereinafter sometimes referred to as "BN aggregate powder of the present invention") is characterized in that the tap density is 0.6 g / ml or more and less than 0.8 g / ml and the interstitial volume of the particles is 0.5 ml / g or more.

[0030] In the present invention, the boron nitride aggregate powder refers to a powder that is an aggregation of boron nitride aggregate particles (hereinafter sometimes simply referred to as "BN aggregate particles").

[0031] [mechanism]

[0032] The details of the mechanism by which a heat sink having excellent thermal conductivity and withstand voltage characteristics can be obtained by the BN aggregate powder of the present invention are not clear, but are presumed as follows.

[0033] When the tap density is less than 0.6 g / ml, there is a tendency for the porosity (particle gap volume) between particles in the BN aggregated powder to increase. If the porosity between particles becomes too large, the probability of generating an area not filled with resin also increases. If a resin sheet containing BN aggregated powder is made and a voltage is applied, leakage occurs in the unfilled resin area, and the voltage resistance deteriorates.

[0034] When the tap density is 0.8 g / ml or more, the porosity between particles in the BN aggregate powder becomes smaller, but if the porosity between particles becomes too small, it is difficult to fill the resin. Therefore, it becomes easy for fine pores to remain in the BN aggregate powder. If a resin sheet containing the BN aggregate powder is made and a voltage is applied, leakage occurs in the unfilled resin area, and the voltage resistance deteriorates.

[0035] In the present invention, the tap density is also related to the growth or growth pattern of the BN primary particles constituting the BN aggregate particles, and is a concept that also includes the amount of closed pores in the BN aggregate particles that cannot be expressed by the porosity.

[0036] When a resin sheet containing BN aggregate powder is prepared using BN aggregate powder having a particle gap volume of less than 0.5 ml / g, the resin component becomes larger relative to the particle gap volume, and the pores remaining in the resin become difficult to remove. Therefore, when a voltage is applied to the obtained resin sheet, electricity leaks in the pores, and the voltage resistance deteriorates.

[0037] The present invention is based on the following discovery: tap density is selected as a comprehensive indicator of the physical properties of BN aggregated particles, such as porosity, particle size distribution, particle shape, particle strength, primary particle size, and amount of closed pores. The tap density of BN aggregated powder is within a very narrow range of above 0.6 g / ml and below 0.8 g / ml. Furthermore, particles with a gap volume of 0.5 ml / g or more have excellent thermal conductivity and voltage resistance when made into heat sinks.

[0038] The tap density in the present invention is the density of the powder filled into the measuring container by tapping measured by the method shown in the items of the embodiments described later. It is believed that the tap density is significantly related to the porosity of the aggregated particles described in Patent Documents 1 and 2, but the tap density is not only related to the porosity of the aggregated particles, but also varies according to the particle size distribution, the shape of the particles, the strength of the particles, the size of the primary particles, the amount of closed pores, etc.

[0039] The interstitial volume of particles in the present invention refers to the cumulative volume of the particles with a pore size of 2 μm or more in mercury intrusion measurement, that is, the amount of interstitial volume between particles when the particles are filled. The interstitial volume of particles is measured by the method described in the section of Examples described below.

[0040] The method of collecting the measurement powder from the BN aggregate powder is not particularly limited, but the powder is preferably mixed uniformly before collecting.

[0041] [BN aggregate powder]

[0042] The BN aggregated powder of the present invention is a collection of BN aggregated particles formed by the aggregation of BN primary particles, preferably h-BN primary particles, and the BN aggregated particles may contain components other than the BN primary particles within a range that does not impair the effects of the present invention. As components other than the h-BN primary particles, components derived from a binder, a surfactant, and a solvent that can be added to the slurry as described in the following [Method for producing BN aggregated powder] can be cited.

[0043] <Shape of BN aggregate particles in BN aggregate powder>

[0044] The shape of the BN aggregated particles in the BN aggregated powder of the present invention is not particularly limited, and may be aggregated particles of any shape such as spherical, ellipsoidal, cylindrical, or hexagonal, which can be produced by aggregating BN primary particles.

[0045] In particular, in order to obtain higher thermal conductivity, preferably, a paper-house-shaped BN aggregated particle having a paper-house-shaped structure is used. The paper-house-shaped structure is described in Ceramics 43No.2 (published by the Japan Ceramic Society in 2008), for example, and is a structure in which plate-like particles are not oriented but are complexly stacked. More specifically, the BN aggregated particles having a paper-house-shaped structure are aggregates of BN primary particles, and are BN aggregated particles having a structure in which the planar portion of the BN primary particles is in contact with the end face portion, preferably in a spherical shape. In addition, the paper-house-shaped structure is preferably the same structure inside the particle. The aggregation morphology and internal structure of these BN aggregated particles can be confirmed by a scanning electron microscope (SEM).

[0046] <Physical properties of BN aggregate powder>

[0047] (Tap density)

[0048] The BN aggregate powder of the present invention is characterized in that a tap density is 0.6 g / ml or more and less than 0.8 g / ml.

[0049] If the tap density is not within the range of 0.6 g / ml or more and less than 0.8 g / ml, the object of the present invention to improve thermal conductivity and withstand voltage characteristics cannot be achieved.

[0050] The tap density of the BN aggregate powder of the present invention is 0.6 g / ml or more, preferably 0.61 g / ml or more, more preferably 0.63 g / ml or more, and further preferably 0.65 g / ml or more. In addition, it is lower than 0.8 g / ml, preferably 0.79 g / ml or less, and more preferably 0.78 g / ml or less. Furthermore, it is 0.6 g / ml or more and lower than 0.8 g / ml, preferably 0.61 g / ml to 0.79 g / ml, and more preferably 0.63 to 0.78 g / ml. By having the tap density in the above range, there is a tendency for thermal conductivity and withstand voltage characteristics to be further improved.

[0051] (Interstitial volume between particles)

[0052] The BN aggregate powder of the present invention is characterized in that the intergranular volume is 0.5 ml / g or more. When the intergranular volume is equal to or greater than the above lower limit, thermal conductivity and withstand voltage characteristics can be improved.

[0053] The intergranular volume of the BN aggregate powder of the present invention is 0.5 ml / g or more, preferably 0.55 ml / g or more, more preferably 0.58 ml / g or more, and further preferably 0.6 ml / g or more. In addition, it is preferably 0.9 ml / g or less, and more preferably 0.8 ml / g or less. By making the intergranular volume within the above range, the amount of resin between the BN aggregate particles when the sheet is formed becomes appropriate, the pores (voids) in the sheet are suppressed, and the thermal conductivity and withstand voltage characteristics tend to be further improved.

[0054] (Volume average particle size (D 50 ))

[0055] The volume average particle size (D 50 ) is not particularly limited, but is preferably 20 μm or more, more preferably 25 μm or more, further preferably 26 μm or more, particularly preferably 30 μm or more, and most preferably 40 μm or more. 50 It is preferably 200 μm or less, more preferably 150 μm or less, further preferably 100 μm or less, and particularly preferably 80 μm or less. 50 When the above lower limit is exceeded, the contact resistance between the BN aggregate particles is suppressed when the heat sink is made, and the thermal conductivity of the BN aggregate powder itself tends to be increased. 50 When the content is not more than the upper limit, the surface smoothness of a heat sink is improved, and the gaps between BN aggregated particles become appropriate, thereby tending to improve the thermal conductivity.

[0056] Here, the volume average particle size (D 50 ) refers to the particle size when the cumulative volume is 50% when the cumulative curve is drawn with the volume of the powder to be measured being 100%. 50 As a wet measurement method, the following method can be cited: using a laser diffraction / scattering particle size distribution measuring device, etc., to measure a sample obtained by dispersing BN aggregate powder in a pure water medium containing sodium hexametaphosphate as a dispersion stabilizer. As a dry measurement method, a method of measuring using "Morphologi" manufactured by Malvern can be cited.

[0057] (Intra-particle porosity)

[0058] The intra-particle porosity of the BN aggregated particles contained in the BN aggregated powder of the present invention is not particularly limited, but is preferably 40% or more, more preferably 45% or more. In addition, it is preferably 60% or less, more preferably 55% or less. When the intra-particle porosity is within the above range, there is a tendency that a heat sink with excellent voltage resistance can be stably manufactured.

[0059] Regarding the intra-particle porosity of BN aggregate particles, the powder density, total pore volume, and inter-particle volume were measured using a mercury porosimeter. The intra-particle pore volume was calculated by subtracting the inter-particle volume from the total pore volume. The ratio of the intra-particle pore volume to the volume of the powder (1 / powder density) was set as the intra-particle porosity.

[0060] (Average circularity)

[0061] The average circularity of the BN aggregate powder of the present invention is not particularly limited, and is preferably 0.8 or more, and more preferably 0.85 or more. The upper limit of the average circularity is not particularly limited, and may be 1. When the average circularity is within the above range, the intergranular volume is within a suitable range, and the effect of the present invention tends to be easily exerted.

[0062] The average circularity of the BN aggregate powder was determined by dispersing the BN aggregate powder using Morphologi G3S manufactured by Malvern Corporation using a pressure pulse sample dispersing unit and analyzing the image.

[0063] (Compression failure strength)

[0064] The compression failure strength of the BN aggregate powder of the present invention is not particularly limited, but is preferably 20 MPa or less, more preferably 15 MPa or less, further preferably 10 MPa or less, and particularly preferably 9 MPa or less. In addition, the compression failure strength is preferably 1 MPa or more, more preferably 2 MPa or more, and further preferably 3 MPa or more. When the compression failure strength is within the above range, the BN aggregate powder can be appropriately deformed, and when a heat sink is manufactured, the thermal conductivity of the heat sink tends to be improved.

[0065] The compression failure strength of BN aggregate powder is measured using Shimadzu Micro Compression Tester MCT-510 manufactured by Shimadzu Corporation at room temperature (20-30°C) with a test force of 98mN, a load speed of 4.84mN / sec, and a flat φ100μm upper pressure head. During the measurement, one BN aggregate particle with a particle size of about 50μm was selected for the test, and this step was performed 5 times, and the compression failure strength was calculated using the average value of the 5 times. The compression failure strength is calculated using the following formula.

[0066] Cs=2.48 / πd 2

[0067] Cs: Compression strength (MPa)

[0068] P: Destructive test force (N)

[0069] d: particle size (mm)

[0070] (Elastic modulus)

[0071] The elastic modulus of the BN aggregate powder of the present invention is not particularly limited, but is preferably 40 MPa or more, more preferably 45 MPa or more, and further preferably 50 MPa or more. In addition, the elastic modulus is preferably 100 MPa or less, and more preferably 90 MPa or more. When the elastic modulus is within the above range, the BN aggregate particles can be appropriately deformed, and when a heat sink is manufactured, the thermal conductivity of the heat sink tends to be improved.

[0072] The elastic modulus of BN aggregated powder is calculated according to the following formula using the test force (N), compression displacement (mm), and particle size (mm) obtained from a compression test of BN aggregated particles (compression test conducted using a Shimadzu micro compression tester at room temperature (20-30°C)) with reference to Physical Property Research, Tanaka Yoshimi, 85(4), 499-518, 2006.

[0073] E=3×(1-ν 2 )×P / 4×(d / 2) 1 / 2 ×Y 3 / 2

[0074] ν: Poisson's ratio (Poisson's ratio is set to 0.13)

[0075] P: Test force (N)

[0076] d: particle size (mm)

[0077] Y: Compression displacement (mm)

[0078] [Method for producing BN aggregate powder]

[0079] The method for producing the BN aggregated powder of the present invention is not limited, but it is particularly preferred that the boron nitride to be the raw material (hereinafter sometimes referred to as "raw material BN powder") is pulverized in a pulverizing step, agglomerated in a granulating step, thereby granulating, and then subjected to a heating step for heat treatment. More specifically, it is preferred that the raw material BN powder is temporarily dispersed in a medium to prepare a slurry of the raw material BN powder (hereinafter sometimes referred to as "BN slurry"), and then pulverized, and then the obtained slurry is used to granulate into spherical particles, and a heating treatment is performed to crystallize the granulated BN granulated powder.

[0080] <Raw material BN powder>

[0081] As the raw material BN powder, any of commercially available h-BN, commercially available α and β-BN, BN produced by a reduction nitridation method of a boron compound and ammonia, BN synthesized from a boron compound and a nitrogen-containing compound such as melamine, etc. can be used without limitation. As the raw material BN powder, h-BN is particularly preferably used in terms of more effectively exerting the effects of the present invention.

[0082] As the form of raw material BN powder, it is suitable to be a powdered BN particle with a wide half-value width of the peak measured by powder X-ray diffraction and low crystallinity. That is, although plate-like h-BN can also be used as a raw material, non-plate-like nanoparticles can also be used appropriately. As a standard of crystallinity, the peak half-value width of the (002) plane measured by powder X-ray diffraction is usually 0.4° or more, preferably 0.45° or more, and more preferably 0.5° or more at an angle of 2θ. In addition, the peak half-value width of the (002) plane is usually 2.0° or less, preferably 1.5° or less, and more preferably 1° or less. The peak half-value width of the (002) plane is below the above upper limit, and there is a tendency that the growth of microcrystals becomes easy and the productivity is fully improved. The peak half-value width of the (002) plane is above the above lower limit, and there is a tendency that the crystallinity becomes an appropriate range, the crystal growth becomes easy, and the dispersion stability when making the slurry is improved.

[0083] The method for producing the raw material BN powder is not particularly limited, and examples thereof include the method described in Microstructural development with crystallization of hexagonal boron nitride (TSUYOSHI etc. JOURNAL OF MATERIALS SCIENCE LETTERS 16 (1997) 795-798) and the like.

[0084] From the perspective of BN crystal growth, it is preferred that a certain amount of oxygen atoms exist in the raw material BN powder. In the present invention, the total oxygen concentration in the raw material BN powder is preferably 1% by weight or more, more preferably 2% by weight or more, further preferably 3% by weight or more, particularly preferably 4% by weight or more, and preferably 10% by weight or less, more preferably 9% by weight or less. When the total oxygen concentration is below the upper limit, there is a tendency that the residual oxygen after heat treatment is suppressed and the improvement effect of thermal conductivity becomes higher. When the total oxygen concentration is above the lower limit, there is a tendency that the crystallinity does not become excessive and crystal growth is obtained.

[0085] Examples of methods for adjusting the total oxygen concentration of the raw BN powder to the above range include a method of synthesizing BN at a low temperature of 1500° C. or lower, and a method of heat treating the raw BN powder in a low temperature oxidizing atmosphere of 500 to 900° C.

[0086] The total oxygen concentration of the raw material BN powder can be measured by an inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer manufactured by Horiba, Ltd.

[0087] The total pore volume of the raw material BN powder is preferably 1.5 cm 3 / g or less. Through the total pore volume of 1.5cm 3 / g or less, the raw material BN powder becomes compact, so that granulation with high sphericity can be achieved. The lower limit of the total pore volume is not particularly limited, but is preferably 0.3 cm 3 / g or more, more preferably 0.5cm 3 / g or above.

[0088] The specific surface area of ​​the raw material BN powder is preferably 50 m 2 / g or more, more preferably 60m 2 / g or more, more preferably 70m 2 / g or more, and preferably 1000m 2 / g or less, more preferably 500m 2 / g or less, more preferably 300m 2 / g or less. The specific surface area of ​​the raw material BN powder is 50m 2 / g or more is preferred because the dispersed particle size in the BN slurry used for sphericalization by granulation can be reduced. The specific surface area of ​​the raw material BN powder is 1000m 2 / g or less is preferred because an increase in slurry viscosity can be suppressed.

[0089] The total pore volume of the raw material BN powder can be measured by nitrogen adsorption method and mercury porosimetry.

[0090] The specific surface area of ​​the raw material BN powder can be measured by the Bouert one-point method (BET 1-point method, adsorption gas: nitrogen). It should be noted that the nitrogen adsorption method is implemented by a method in accordance with JIS Z8830, and the measurement temperature is set to -196°C (liquid nitrogen temperature). In addition, the mercury intrusion method is implemented by a method in accordance with JIS R1655, and the surface tension of BN is set to 485 dyn / cm 2 , the contact angle was set to 140°, and the measurement temperature was set to 23-26°C.

[0091] <Medium>

[0092] The medium used for preparing the BN slurry is not particularly limited, and water and / or various organic solvents can be used. From the viewpoint of ease of spray drying and simplification of the apparatus, water is preferably used as the medium, and pure water is more preferably used.

[0093] The medium used for preparing the BN slurry is preferably added in an amount that makes the viscosity of the BN slurry 200 to 5000 mPa·s. The viscosity of the BN slurry refers to the viscosity when the slurry temperature is 10°C or higher and 60°C or lower, and preferably, the above viscosity is achieved at a temperature of preferably 15°C or higher and 50°C or lower, more preferably 15°C or higher and 40°C or lower, and further preferably 15°C or higher and 35°C or lower.

[0094] Specifically, the amount of the medium used for the preparation of the BN slurry is preferably 10% by weight or more relative to the BN slurry, more preferably 20% by weight or more, and more preferably 30% by weight or more, and preferably 70% by weight or less, more preferably 65% ​​by weight or less, and more preferably 60% by weight or less. If the amount of the medium is below the upper limit, the slurry viscosity will not become too low, so the sedimentation is suppressed, and the uniformity of the BN slurry is obtained. Therefore, the tap density of the obtained BN aggregated particles tends to be within the desired range. By using a medium above the lower limit, the slurry viscosity will not become too high, and granulation tends to become easy.

[0095] <Surfactant>

[0096] From the viewpoint of adjusting the viscosity of the slurry and the viewpoint of the dispersion stability (aggregation suppression) of the raw material BN powder in the slurry, various surfactants may be added to the BN slurry.

[0097] As the surfactant, an anionic surfactant, a cationic surfactant, a nonionic surfactant, etc. can be used. These may be used alone or in combination of two or more.

[0098] Generally, a surfactant can change the viscosity of the slurry. Therefore, when a surfactant is added to the BN slurry, the amount thereof is adjusted to an amount such that the viscosity of the BN slurry is 200 to 5000 mPa·s. It should be noted that the viscosity of the BN slurry represents the viscosity in the temperature range described in the medium for preparing the BN slurry.

[0099] For example, when using BN with a half-value width 2θ of 0.67° and a total oxygen concentration of 7.5 wt% as raw material BN to prepare a slurry with a solid content of 50 wt%, an anionic surfactant is usually used as an effective ingredient, preferably 0.01 wt% or more, more preferably 0.05 wt% or more, and further preferably 0.1 wt% or more relative to the total amount of the slurry, and preferably 10 wt% or less, more preferably 7 wt% or less, further preferably 5 wt% or less, and particularly preferably 3 wt% or less. By adding an amount below the upper limit, there is a tendency to suppress the decrease in slurry viscosity, and the carbon component from the surfactant is not easily retained in the generated BN aggregate particles. By adding an amount above the lower limit, there is a tendency to suppress the slurry viscosity from becoming too high, and granulation becomes easy.

[0100] <Binder>

[0101] In order to efficiently granulate the raw material BN powder into particles, the BN slurry may contain a binder. The binder plays a role in firmly linking the BN primary particles to stabilize the granulated particles.

[0102] The binder used in the BN slurry may be any binder that can improve the adhesion between the BN particles. In the present invention, the granulated particles are subjected to a heat treatment after being granulated, so a binder having heat resistance to the high temperature conditions in the heat treatment step is preferred.

[0103] As such a binder, it is preferred to use metal oxides such as aluminum oxide, magnesium oxide, yttrium oxide, calcium oxide, silicon oxide, boron oxide, cerium oxide, zirconium oxide, and titanium oxide. Among these, aluminum oxide and yttrium oxide are preferred from the viewpoints of thermal conductivity and heat resistance as oxides and the bonding force for bonding BN particles to each other.

[0104] The binder may be a liquid binder such as alumina sol, or may be a binder that reacts during heating and is converted into other inorganic components.

[0105] These binders may be used alone or in combination of two or more.

[0106] The binder may be included or not included, and may be 0% by weight relative to the raw material BN powder in the BN slurry. In addition, the amount of the binder when included (the amount in terms of solid content in the case of a liquid binder) is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, and further preferably 1.0% by weight or more, and preferably 30% by weight or less, more preferably 20% by weight or less, and further preferably 15% by weight or less. When the amount of the binder is below the upper limit, crystal growth is obtained, and when used as a thermally conductive filler, a thermal conductivity improvement effect tends to be obtained.

[0107] <BN slurry preparation method>

[0108] The method for preparing the BN slurry is not particularly limited as long as the raw material BN powder and the medium, and the binder and surfactant as needed are uniformly dispersed and adjusted to a desired viscosity range. When using the raw material BN powder and the medium, and the binder and surfactant as needed, the BN slurry is preferably prepared as follows.

[0109] A predetermined amount of raw material BN powder is weighed and placed in a resin bottle, and then a predetermined amount of binder is added. Then, a predetermined amount of surfactant is added, and then zirconium oxide ceramic beads are added, and stirred on a pot mill rotating table for about 0.5 to 5 hours until the desired viscosity is reached.

[0110] The order of addition is not particularly limited. When a large amount of raw material BN powder is slurried, in order to facilitate the formation of aggregates such as agglomerates, a prescribed amount of raw material BN powder may be added in small amounts in sequence after preparing an aqueous solution obtained by adding a surfactant and a binder to water, and zirconia ceramic beads may be added thereto, and the mixture may be dispersed and slurried using a pot mill rotary table.

[0111] For dispersion, a dispersion device such as a bead mill, a planetary mixer, etc. may be used in addition to a pot mill.

[0112] When slurrying is performed, the temperature of the slurry is preferably 10° C. to 60° C. When the slurry temperature is above the lower limit, an increase in the slurry viscosity tends to be suppressed, and when the slurry temperature is below the upper limit, decomposition of the raw material BN powder into ammonia in the slurry tends to be suppressed.

[0113] The temperature of the slurry is more preferably 15°C to 50°C, further preferably 15°C to 40°C, and particularly preferably 15°C to 35°C.

[0114] <Granulation>

[0115] In order to obtain granulated powder from BN slurry, a common granulation method such as a spray drying method, a tumbling method, a fluidized bed method, a stirring method, etc. can be used. Among them, the spray drying method is preferred.

[0116] By spray drying, granulated powder of a desired size can be produced by adjusting the concentration of the slurry used as the raw material, the amount of liquid introduced into the device per unit time, and the compressed air pressure and compressed air volume when the slurry is sprayed. Spherical granulated powder can also be obtained by spray drying.

[0117] The spray drying device used is not limited, but in order to produce larger spherical granulated powder, a device using a rotating disk is most suitable. Examples of such devices include the spray dryer F series manufactured by Okawara Chemical Industry Co., Ltd., the spray dryer "MDL-050M" manufactured by Fujisaki Electric Co., Ltd., and the spray dryer "P260" manufactured by PRECI Co., Ltd.

[0118] The average particle size of the granulated powder obtained by granulation is calculated by subtracting the volume-based average particle size D of the BN aggregate powder of the present invention from that of the granulated powder. 50 When the range is set to 20 μm or more and 200 μm or less, it is preferred that the average particle size D based on volume 50 The thickness is preferably 10 μm or more, more preferably 15 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less.

[0119] The volume-based average particle size D of the granulated powder 50 For example, in the case of a wet method, it can be measured by "LA920" manufactured by Horiba, Ltd., and in the case of a dry method, it can be measured by "Morphorogi" manufactured by Malvern, etc.

[0120] <Heat treatment>

[0121] The BN granulated powder can be further subjected to a heat treatment in a non-oxidizing gas atmosphere to produce a BN aggregate powder.

[0122] The non-oxidizing gas atmosphere refers to an atmosphere such as nitrogen, helium, argon, ammonia, hydrogen, methane, propane, carbon monoxide, etc. The crystallization rate of BN aggregate particles varies depending on the type of atmosphere gas used here. In order to perform crystallization in a short time, it is particularly suitable to use nitrogen or a mixed gas formed by using nitrogen and other gases.

[0123] The heat treatment temperature is preferably 1600° C. or higher, more preferably 1800° C. or higher, and preferably 2300° C. or lower, more preferably 2200° C. or lower. When the heat treatment temperature is above the lower limit, the growth of the average crystallite of the BN primary particles is sufficiently obtained, and the thermal conductivity of the BN aggregate powder tends to increase. When the heat treatment temperature is below the upper limit, the decomposition of the BN aggregate powder tends to be suppressed.

[0124] The heat treatment time is preferably 5 hours or more and 20 hours or less, more preferably 5 hours or more and 15 hours or less. When the heat treatment time is above the lower limit, crystal growth can be fully obtained. When the heat treatment time is below the upper limit, there is a tendency to suppress the decomposition of BN.

[0125] Since the heat treatment is carried out under a non-oxidizing gas atmosphere, it is preferred that a vacuum pump is usually used to exhaust the baking furnace, and then a non-oxidizing gas is introduced while heating and heating to a desired temperature. When the non-oxidizing gas can be fully replaced in the baking furnace, it is also possible to heat and heat while introducing a non-oxidizing gas at normal pressure. As the baking furnace, batch furnaces such as muffle furnaces, tubular furnaces, and atmosphere furnaces or continuous furnaces such as rotary kilns, screw conveyor furnaces, tunnel kilns, belt furnaces, push furnaces, and vertical continuous furnaces can be listed, and use can be distinguished according to the purpose.

[0126] Usually, in order to reduce the non-uniformity of the composition during calcination, the granulated powder to be heated is placed in a circular graphite covered crucible for heating and calcining. At this time, in addition to reducing the non-uniformity of the composition, a graphite spacer may be inserted for the purpose of suppressing the sintering of the BN aggregated particles caused by calcination. There is no particular restriction on the number of divisions using the spacer as long as sintering can be suppressed, and it is usually more than 2 divisions and less than 16 divisions. When the number of divisions is above the upper limit, there is a tendency that sintering is suppressed and the crystals of the h-BN primary particles grow fully. When the number of divisions is above the lower limit, there is a tendency that sintering can be suppressed.

[0127] <Classification>

[0128] In order to reduce the particle size distribution and suppress the viscosity increase when compounded in a resin composition containing BN aggregate powder, the BN aggregate powder after the above-mentioned heat treatment is preferably subjected to classification treatment. The classification is usually performed after the granulated powder is heated, and can also be performed on the granulated powder before heating treatment and then subjected to heating treatment.

[0129] The classification may be either wet or dry, but dry classification is preferred from the viewpoint of suppressing the decomposition of BN. When the binder is water-soluble, dry classification is particularly preferred.

[0130] In addition to the classification using a sieve, there is also wind classification that uses the difference between centrifugal force and fluid resistance to perform classification. Dry classification can also be performed using a classifier such as a cyclonic airflow classifier, a forced vortex centrifugal classifier, and a semi-free vortex centrifugal classifier. These classifiers can be appropriately differentiated and used according to the particle size of the particles to be classified, such as using a cyclonic airflow classifier when classifying smaller microparticles in the single micron region from submicron, and using a semi-free vortex centrifugal classifier when classifying relatively larger particles above that.

[0131] <Method for obtaining BN aggregate powder of the present invention>

[0132] The method for producing the BN aggregate powder of the present invention having a tap density of 0.6 g / ml or more and less than 0.8 g / ml and a particle interstitial volume of 0.5 ml / g or more is not particularly limited, and the following methods may be mentioned.

[0133] The method for obtaining the BN aggregate powder of the present invention includes a method of collecting the heat-treated powder at a certain distance inside the inner wall surface of the crucible instead of the inner wall surface side of the crucible after the heat treatment.

[0134] The vicinity of the inner wall surface of the crucible tends to be greatly affected by the material of the crucible and the material of the heating furnace, and thus BN aggregate particles tend to be obtained with a tap density that exceeds the range defined in the present invention and is large.

[0135] On the other hand, the inner side of the crucible (the area at a certain distance from the inner wall of the crucible) tends to be less affected by the crucible material and the heating furnace material. Therefore, there is a tendency to obtain BN aggregate particles having a tap density within the range specified in the present invention from near the center of the crucible.

[0136] In addition, the tap density and intergranular volume of the BN aggregated powder vary according to the growth of the BN primary particles and the shape of the BN aggregated particles, and the particle growth of the BN primary particles or the shape of the BN aggregated particles varies according to the oxygen concentration contained in the BN raw material. Therefore, by controlling the oxygen concentration while performing a heat treatment, the tap density and intergranular volume can be adjusted to within the limited range of the present invention. Specifically, there can be cited: a method of heating under the condition of coexistence of carbon as a reducing agent, or a method of adjusting the oxygen concentration under reduced pressure, etc.

[0137] Furthermore, as an oxygen concentration control method other than the above, there is mentioned a method of providing a plurality of heat treatment steps, maintaining the BN primary particles in the crystal growth temperature range for a long time, and then performing heat treatment at a temperature higher than the crystal growth temperature range.

[0138] The above methods may be used alone or in combination.

[0139] [Resin composition containing BN aggregate powder]

[0140] When manufacturing the heat sink of the present invention containing the BN aggregate powder of the present invention, generally, a resin composition containing at least the BN aggregate powder of the present invention as an inorganic filler and a resin (hereinafter sometimes referred to as "the composition containing the BN aggregate powder of the present invention" or "the composition of the present invention") is prepared, and the prepared composition of the present invention is molded into a sheet to produce the heat sink of the present invention. The composition containing the BN aggregate powder of the present invention is described below.

[0141] The resin composition containing BN aggregate powder of the present invention generally comprises a resin component, preferably a thermosetting resin component, an inorganic filler containing the BN aggregate powder of the present invention, a curing agent, a curing catalyst, other components used as needed, a solvent for preparing a coating slurry, and the like.

[0142] When the composite molded body described below is formed, the composition of the present invention preferably further contains a compound having a nitrogen atom and a heterocyclic structure from the viewpoint of improving adhesion to metal.

[0143] [Ingredients other than inorganic fillers]

[0144] <Thermosetting resin component>

[0145] The thermosetting resin included in the composition of the present invention is not particularly limited as long as it is cured in the presence of a curing agent or a curing catalyst. As thermosetting resins, specifically, epoxy resins, phenolic resins, polycarbonate resins, unsaturated polyester resins, polyurethane resins, melamine resins, urea resins, etc. can be cited. Among these, epoxy resins are preferred from the perspectives of viscosity, heat resistance, hygroscopicity, and operability. As epoxy resins, for example, epoxy compounds containing epoxy groups, aliphatic epoxy resins, bisphenol A or F type epoxy resins, novolac type epoxy resins, alicyclic epoxy resins, glycidyl ester type epoxy resins, multifunctional epoxy resins, polymer epoxy resins, etc. can be cited.

[0146] (Epoxy resin)

[0147] Epoxy resin is a general term for compounds having one or more oxirane rings (epoxy groups) in the molecule.

[0148] The oxirane ring (epoxy group) contained in the epoxy resin may be any of an alicyclic epoxy group and a glycidyl group, but a glycidyl group is more preferable from the viewpoint of reaction rate and heat resistance.

[0149] The epoxy resin used in the present invention may be a compound containing an aromatic oxirane ring (epoxy group). Specific examples thereof include bisphenol-type epoxy resins obtained by glycidylating bisphenols such as bisphenol A, bisphenol F, bisphenol AD, bisphenol S, tetramethylbisphenol A, tetramethylbisphenol F, tetramethylbisphenol AD, tetramethylbisphenol S, and tetrafluorobisphenol A; biphenyl-type epoxy resins; epoxy resins obtained by glycidylating diphenols such as dihydroxynaphthalene and 9,9-bis(4-hydroxyphenyl)fluorene; epoxy resins obtained by glycidylating triphenols such as 1,1,1-tris(4-hydroxyphenyl)methane; epoxy resins obtained by glycidylating tetraphenols such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane; and novolac-type epoxy resins obtained by glycidylating novolacs such as phenol novolac, cresol novolac, bisphenol A novolac, and brominated bisphenol A novolac.

[0150] An epoxy resin suitable as the epoxy resin used in the present invention (hereinafter sometimes referred to as a "specific epoxy resin") and a polyfunctional epoxy resin preferably used in combination with the specific epoxy resin will be described below.

[0151] Hereinafter, the term "organic group" includes any group as long as it contains carbon atoms, and examples thereof include alkyl groups, alkenyl groups, aryl groups, etc. These may be substituted with halogen atoms, groups having heteroatoms, or other hydrocarbon groups.

[0152] (Specific epoxy resin)

[0153] Examples of the specific epoxy resin include epoxy resins having at least one structure selected from the group consisting of a structure represented by the following structural formula (1) (hereinafter sometimes referred to as “structure (1)”) and a structure represented by the following structural formula (2) (hereinafter sometimes referred to as “structure (2)”).

[0154]

[0155] In formula (1), R 1 and R 2 Each of them represents an organic group, and at least one of them is an organic group with a molecular weight of 16 or more. 3 It represents a divalent cyclic organic group.

[0156] Examples of the specific epoxy resin include epoxy resins having a structure represented by the following structural formula (3) (hereinafter sometimes referred to as “structure (3)”).

[0157]

[0158] In formula (3), R 4 , R 5 , R 6 , R7 They respectively represent an organic group having a molecular weight of 15 or more.

[0159] In the above formula (1), R 1 and R 2 At least one of them represents an organic group having a molecular weight of 16 or more, preferably a molecular weight of 16 to 1000. Examples of the organic group having a molecular weight of 16 or more include alkyl groups such as ethyl, propyl, butyl, pentyl, hexyl, and heptyl, and aryl groups such as phenyl, tolyl, xylyl, naphthyl, and fluorenyl. 1 and R 2 Both may be organic groups with a molecular weight of 16 or more, or one may be an organic group with a molecular weight of 16 or more and the other may be an organic group with a molecular weight of 15 or less or a hydrogen atom. 1 and R 2 One of them is an organic group having a molecular weight of 16 or more, and the other is an organic group having a molecular weight of 15 or less. In terms of easy control of operability such as resin viscosity and the strength of the cured product, R is particularly preferred. 1 and R 2 One of them is methyl and the other is phenyl.

[0160] In formula (2), R 3 It is a divalent cyclic organic group, which may be an aromatic ring structure such as a benzene ring structure, a naphthalene ring structure, a fluorene ring structure, or an aliphatic ring structure such as cyclobutane, cyclopentane, and cyclohexane. In addition, they may also independently have substituents such as hydrocarbon groups or halogen atoms. The divalent bonding part may be a divalent group located at a single carbon atom, or may be a divalent group located at different carbon atoms. Preferred examples include: a divalent aromatic group having 6 to 100 carbon atoms, and a group derived from a cycloalkane having 2 to 100 carbon atoms such as cyclopropane or cyclohexane. From the perspective of controlling the operability of the resin viscosity or the strength of the cured product, R 3 Particularly preferred is 3,3,5-trimethyl-1,1-cyclohexylene represented by the following structural formula (4).

[0161]

[0162] In formula (3), R 4 , R 5 , R 6 , R 7 Each of them is an organic group having a molecular weight of 15 or more, preferably an alkyl group having a molecular weight of 15 to 1000. In terms of control of workability such as resin viscosity and strength of the cured product, R 4 , R 5 , R 6 , R 7 All are methyl.

[0163] From the viewpoint of achieving both reduced hygroscopicity and strength retention of the heat sink obtained as a cured product, the specific epoxy resin is particularly preferably an epoxy resin containing any of the structures (1) and (2) and the structure (3).

[0164] Such a specific epoxy resin contains more hydrophobic hydrocarbons and aromatic structures than conventional epoxy resins having a bisphenol A or bisphenol F skeleton. Therefore, by blending the specific epoxy resin, the moisture absorption of the heat sink, which is the obtained cured product, can be reduced.

[0165] From the viewpoint of reducing the moisture absorption, the specific epoxy resin preferably contains a large amount of structures (1), (2), and (3) which are hydrophobic structures. Specifically, it is preferably an epoxy resin having a weight average molecular weight of 10,000 or more, more preferably an epoxy resin having a weight average molecular weight of 20,000 or more, and further more preferably an epoxy resin having a weight average molecular weight of 30,000 or more, for example, 30,000 to 40,000.

[0166] The specific epoxy resin is preferably more hydrophobic. Specifically, the epoxy equivalent of the specific epoxy component is preferably large, preferably 5000 g / equivalent or more, more preferably 7000 g / equivalent or more, for example 8000 to 15000 g / equivalent.

[0167] Here, the weight average molecular weight of the epoxy resin is a value in terms of polystyrene measured by gel permeation chromatography.

[0168] The epoxy equivalent is defined as "the weight of an epoxy resin containing 1 equivalent of epoxy groups", and can be measured in accordance with JIS K7236.

[0169] Such specific epoxy resins may be used alone or in combination of two or more.

[0170] (Multifunctional epoxy resin)

[0171] The multifunctional epoxy resin refers to an epoxy resin having three or more oxirane rings (epoxy groups) per molecule.

[0172] From the viewpoint of increasing the storage modulus of the cured product after thermal curing, especially increasing the storage modulus at high temperatures which is important when a large amount of heat is released, such as in power semiconductors, an epoxy resin having two or more ethylene oxide rings (epoxy groups) in the molecule is preferred, an epoxy resin having three or more ethylene oxide rings (epoxy groups) in the molecule is more preferred, and an epoxy resin having four or more glycidyl groups in the molecule is even more preferred.

[0173] By having a plurality of ethylene oxide rings (epoxy groups), especially glycidyl groups, in the molecule, the crosslinking density of the cured product is increased, and the strength of the cured product, i.e., the heat sink, is higher. As a result, when internal stress is generated in the heat sink during the moisture absorption reflow test, the heat sink does not deform or break but maintains its shape, thereby suppressing the generation of voids such as cavities in the heat sink material.

[0174] The molecular weight of the multifunctional epoxy resin is preferably 1,000 or less, particularly preferably 100 to 800, from the viewpoint of increasing the storage elastic modulus of the heat dissipation sheet after thermal curing.

[0175] By adding a multifunctional epoxy resin, oxirane rings (epoxy groups) with high polarity can be introduced at a high density, thereby enhancing the effect of physical interactions such as van der Waals forces or hydrogen bonds, and improving the adhesion between the metal in the composite molded body described below and the heat sink of the present invention as a resin cured product. In addition, by adding a multifunctional epoxy resin, the storage modulus of the heat sink after heat curing can be increased, and thus, the cured product of the thermosetting resin composition enters the unevenness of the metal as the adherend to show a strong anchoring effect, which can improve the adhesion between the metal and the heat sink.

[0176] On the other hand, the hygroscopicity of the thermosetting resin composition tends to increase by introducing a multifunctional epoxy resin, but by increasing the reactivity of the oxirane ring (epoxy group), the amount of hydroxyl groups in the middle of the reaction can be reduced, thereby suppressing the increase in hygroscopicity. In addition, by combining the above-mentioned specific epoxy resin with a multifunctional epoxy resin to produce a thermosetting resin composition, it is possible to achieve both high elasticity and low hygroscopicity of the obtained heat sink.

[0177] Specifically, the polyfunctional epoxy resin is preferably an epoxy resin having three or more epoxy groups, and for example, EX321L, DLC301, DLC402, etc. manufactured by Nagase ChemteX can be used.

[0178] These multifunctional epoxy resins may be used alone or in combination of two or more.

[0179] (content)

[0180] The composition of the present invention preferably contains 5% by weight or more, especially 50% by weight or more, and 99% by weight or less, especially 98% by weight or less of a thermosetting resin component in 100% by weight of the composition of the present invention excluding the solvent and the inorganic filler. If the content of the thermosetting resin component is above the lower limit, the moldability becomes good. If the content of the curable resin component is below the upper limit, the content of other components can be ensured, and the thermal conductivity can be improved.

[0181] The composition of the present invention preferably contains 20 to 100% by weight, particularly 45 to 100% by weight, of epoxy resin in the thermosetting resin component.

[0182] The composition of the present invention preferably contains 50% by weight or less, especially 40% by weight or less, and 5% by weight or more, especially 10% by weight or more of the above-mentioned specific epoxy resin as the preferred epoxy resin in all epoxy resins. If the content of the specific epoxy resin is above the above lower limit, the above-mentioned effect produced by containing the specific epoxy resin can be effectively obtained. If the specific epoxy resin is too much, the crosslinking density decreases and the cured product becomes brittle. By setting the content of the specific epoxy resin to below the above upper limit, the hygroscopicity of the cured product can be suppressed, and the strength performance of the cured product is excellent, and these properties can be taken into account.

[0183] The composition of the present invention preferably contains 5% by weight or more, especially 10% by weight or more, and 50% by weight or less, especially 40% by weight or less of the above-mentioned multifunctional epoxy resin as the preferred epoxy resin in the total epoxy resin. If the content of the multifunctional epoxy resin is above the above lower limit, the above-mentioned effect produced by containing the multifunctional epoxy resin can be effectively obtained. When the content of the multifunctional epoxy resin is below the above upper limit, the hygroscopicity of the cured product can be suppressed, and the strength performance of the cured product can be made excellent, and these properties can be taken into account.

[0184] In order to simultaneously obtain high elasticity and low hygroscopicity of the obtained cured product, the composition of the present invention preferably contains both a specific epoxy resin and a multifunctional epoxy resin as epoxy resins. In this case, the content ratio of the specific epoxy resin to the multifunctional epoxy resin is preferably specific epoxy resin: multifunctional epoxy resin = 10 to 90: 90 to 10, especially 20 to 80: 80 to 20 (weight ratio).

[0185] The epoxy resin other than the specific epoxy resin and the multifunctional epoxy resin contained in the composition of the present invention is not particularly limited, and is preferably selected from various bisphenol-type epoxy resins obtained by glycidylating bisphenols such as bisphenol A-type epoxy resin and bisphenol F-type epoxy resin, various biphenyl-type epoxy resins obtained by glycidylating biphenyls, and aromatic compounds having two hydroxyl groups such as dihydroxynaphthalene and 9,9-bis(4-hydroxyphenyl)fluorene. One or more of the following: epoxy resins obtained by glycidylating triphenols such as 1,1,1-tris(4-hydroxyphenyl)methane, epoxy resins obtained by glycidylating tetraphenols such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, novolac-type epoxy resins obtained by glycidylating novolacs such as phenol novolac, cresol novolac, bisphenol A novolac, brominated bisphenol A novolac, and epoxy resins containing silicone.

[0186] <Compounds containing nitrogen atoms and having a heterocyclic structure>

[0187] The compound containing a nitrogen atom and having a heterocyclic structure (hereinafter sometimes referred to as a "nitrogen-containing heterocyclic compound") exerts an effect of improving the adhesion between the cured product of the composition of the present invention and metal.

[0188] The nitrogen-containing heterocyclic compound is located at their interface when the composition of the present invention is composited with a metal, and improves the adhesion of the composition of the present invention to the metal. From this viewpoint, in order to make the nitrogen-containing heterocyclic compound easily stay at the interface of the composition of the present invention and the metal, the nitrogen-containing heterocyclic compound is more preferably a low molecular weight. The molecular weight of the nitrogen-containing heterocyclic compound is preferably less than 1000, more preferably less than 500.

[0189] Examples of the heterocyclic structure possessed by the nitrogen-containing heterocyclic compound include structures derived from imidazole, triazine, triazole, pyrimidine, pyrazine, pyridine, and azole. From the viewpoint of improving the insulation properties of the thermosetting resin composition and the adhesion to metals, imidazole compounds and triazine compounds are preferred.

[0190] Preferred imidazole compounds and triazine compounds include, for example, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2 '-Ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,4-diamino-6-vinyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine isocyanuric acid adduct, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine isocyanuric acid adduct, etc.

[0191] Among these, the curing speed or the physical properties after curing can be easily adjusted by high resin compatibility and high reaction activation temperature, thereby achieving improved storage stability of the composition of the present invention or further improved bonding strength after heat molding. Particularly preferred are those having a structure derived from imidazole and those having a structure derived from triazine, and more particularly preferred are those having a structure derived from triazine. As the heterocyclic structure possessed by the nitrogen-containing heterocyclic compound, a structure derived from 1,3,5-triazine is particularly preferred. The nitrogen-containing heterocyclic compound may also be one having a plurality of the structural moieties exemplified above.

[0192] The nitrogen-containing heterocyclic compound may contain the following curing catalyst depending on the structure. Therefore, the composition of the present invention may contain a nitrogen-containing heterocyclic compound as a curing catalyst.

[0193] The nitrogen-containing heterocyclic compound may be used alone or in combination of two or more. The nitrogen-containing heterocyclic compound may have a plurality of heterocyclic structures in one molecule.

[0194] The nitrogen-containing heterocyclic compound preferably contains 0.001% by weight or more, especially 0.1% by weight or more, and 10% by weight or less, especially 5% by weight or less in 100% by weight of the composition of the present invention excluding the solvent and the inorganic filler. When the following curing catalyst is contained in the nitrogen-containing heterocyclic compound in terms of its molecular structure, it is preferably that the total amount including their content is contained in the above range. If the content of the nitrogen-containing heterocyclic compound is above the above lower limit, the above-mentioned effect produced by including the compound can be fully obtained. If the content of the nitrogen-containing heterocyclic compound is below the above upper limit, the reaction is effectively carried out, the crosslinking density can be increased, the strength is increased, and then the storage stability is improved.

[0195] <Curing agent>

[0196] As curing agent, there is no particular limitation, and preferred curing agent is phenolic resin, anhydride with aromatic skeleton or alicyclic skeleton, or hydride of the anhydride or modified substance of the anhydride. By using these preferred curing agents, a resin cured product with excellent balance of heat resistance, moisture resistance and electrical properties can be obtained. Curing agent can be used only one, or two or more can be used in combination.

[0197] Phenolic resin is not particularly limited. As a specific example of phenolic resin, phenol novolac, o-cresol novolac, p-cresol novolac, tert-butylphenol novolac, dicyclopentadiene cresol, poly-p-vinylphenol, bisphenol A novolac, benzyl dimethyl modified novolac, decalin modified novolac, poly (di-o-hydroxyphenyl) methane, poly (di-m-hydroxyphenyl) methane or poly (di-p-hydroxyphenyl) methane etc. can be cited. Wherein, in order to further improve the flexibility and flame retardancy of the thermosetting resin composition, improve the mechanical properties and heat resistance of the resin cured product, preferably, the novolac type phenolic resin with a rigid main chain skeleton, the phenolic resin with a triazine skeleton. In order to improve the flexibility of the uncured thermosetting resin composition and the toughness of the resin cured product, preferably, the phenolic resin with an allyl group.

[0198] Commercially available products of the phenolic resin include MEH-8005, MEH-8000H, and NEH-8015 (all manufactured by Meiwa Chemical Co., Ltd.), YLH903 (manufactured by Mitsubishi Chemical Co., Ltd.), LA-7052, LA-7054, LA-7751, LA-1356, and LA-3018-50P (all manufactured by DAINIHON INK Co., Ltd.), and PSM6200, PS6313, and PS6492 (manufactured by Gun-Ei Chemical Co., Ltd.).

[0199] The anhydride having an aromatic skeleton, the hydride of the anhydride or the modified product of the anhydride is not particularly limited. Specific examples include: SMARESIN EF30 and SMARESIN EF60 (all manufactured by Sartomer Japan), ODPA-M and PEPA (all manufactured by MANAC), RIKACID MTA-10, RIKACID TMTA, RIKACID TMEG-200, RIKACID TMEG-500, RIKACID TMEG-S, RIKACID TH, RIKACID MH-700, RIKACID MT-500, RIKACID DSDA and RIKACID TDA-100 (all manufactured by New Japan Chemical Co., Ltd.), EPICLON B4400, and EPICLON B570 (all manufactured by DAINIHON INK Chemical Co., Ltd.), etc.

[0200] The acid anhydride having an alicyclic skeleton, the hydride of the acid anhydride, or the modified product of the acid anhydride is preferably an acid anhydride having a polyalicyclic skeleton, the hydride of the acid anhydride, or the modified product of the acid anhydride, or an acid anhydride having an alicyclic skeleton obtained by an addition reaction of a terpene compound and maleic anhydride, the hydride of the acid anhydride, or the modified product of the acid anhydride. Specific examples include: RIKACID HNA and RIKACID HNA-100 (all of which are manufactured by New Japan Chemical Co., Ltd.), and EPI-CURE YH306 and EPI-CURE YH309 (all of which are manufactured by Mitsubishi Chemical Co., Ltd.).

[0201] The curing agent is preferably contained in 0 to 70% by weight, particularly 0 to 55% by weight, in 100% by weight of the composition of the present invention excluding the solvent and the inorganic filler. If the content of the curing agent is above the above lower limit, sufficient curing performance can be obtained. If the content of the curing agent is below the above upper limit, the reaction proceeds effectively, the crosslinking density can be increased, the strength can be increased, and further, the film forming property is improved.

[0202] <Curing catalyst>

[0203] The composition of the present invention preferably contains a curing catalyst together with the above-mentioned curing agent in order to adjust the curing speed or the physical properties of the cured product.

[0204] The curing catalyst is not particularly limited and can be appropriately selected according to the type of the thermosetting resin component or curing agent used. Specific examples of the curing catalyst include: diazabicycloolefins such as chain or cyclic tertiary amines, organophosphorus compounds, quaternary phosphonium salts or organic acid salts, etc. As the curing catalyst, organometallic compounds, quaternary ammonium salts or metal halides, etc. can also be used. As the above-mentioned organometallic compounds, zinc octoate, tin octoate or acetylacetonate aluminum complex, etc. can be listed.

[0205] These may be used alone or in combination of two or more.

[0206] The curing catalyst preferably contains 0.1 to 10% by weight, especially 0.1 to 5% by weight, in 100% by weight of the composition of the present invention excluding the solvent and the inorganic filler. If the content of the curing catalyst is above the above lower limit, the curing reaction can be fully promoted to cure well. If the content of the curing catalyst is below the above upper limit, the curing speed will not become too fast, and therefore, the storage stability of the composition of the present invention can be made good.

[0207] <Other ingredients>

[0208] The composition of the present invention may also contain other components other than the above as components other than the inorganic filler within the range that does not impair the effect of the present invention. As other components, surface treatment agents such as silane coupling agents that improve the interfacial bonding strength between the inorganic filler and the resin component when using the composition of the present invention to manufacture a cured resin, insulating carbon components such as reducing agents, viscosity modifiers, dispersants, thixotropy imparting agents, flame retardants, colorants, organic fillers, organic solvents, and thermoplastic resins can be listed.

[0209] Among these, the following may be true: by including a dispersant in the composition of the present invention, a uniform cured resin can be formed, and the thermal conductivity and dielectric breakdown characteristics of the obtained cured resin can be improved. In addition, by including an organic filler or a thermoplastic resin in the composition of the present invention, appropriate elongation can be imparted to the composition, the generated stress can be relaxed, and cracking can be suppressed during a temperature cycle test.

[0210] The dispersant preferably contains a functional group containing hydrogen atoms having hydrogen bonding properties. When the dispersant contains a functional group containing hydrogen atoms having hydrogen bonding properties, the thermal conductivity and dielectric breakdown characteristics of the obtained cured product, i.e., the heat sink, can be further improved. Examples of the functional group containing hydrogen atoms having hydrogen bonding properties include: a carboxyl group (pKa=4), a phosphate group (pKa=7), or a phenol group (pKa=10).

[0211] The pKa of the functional group containing hydrogen atoms having hydrogen bonding property is preferably in the range of 2 to 10, and more preferably in the range of 3 to 9. When the pKa is 2 or more, the acidity of the dispersant may be in an appropriate range, and the reaction of the epoxy resin in the thermosetting resin component may be easily suppressed. Therefore, when the uncured molded product is stored, the storage stability tends to be improved. When the pKa is 10 or less, the function as a dispersant tends to be fully exerted, and the thermal conductivity and dielectric breakdown characteristics of the obtained cured product, i.e., the heat sink, tend to be sufficiently improved.

[0212] The functional group containing a hydrogen atom having hydrogen bonding property is preferably a carboxyl group or a phosphoric acid group. If it is these functional groups, the thermal conductivity and dielectric breakdown characteristics of the heat sink can be further improved.

[0213] Specific examples of the dispersant include polyester carboxylic acid, polyether carboxylic acid, polyacrylic acid, aliphatic carboxylic acid, polysiloxane carboxylic acid, polyester phosphoric acid, polyether phosphoric acid, polyacrylic acid, aliphatic phosphoric acid, polysiloxane phosphoric acid, polyester phenol, polyether phenol, polyacrylic acid phenol, or polysiloxane phenol. The dispersant may be used alone or in combination of two or more.

[0214] As the thermoplastic resin, any commonly known thermoplastic resin can be used. For example, polyethylene, polypropylene, polystyrene, polyvinyl chloride, (meth) acrylic resin, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer and other vinyl polymers, polylactic acid resin, polyethylene terephthalate, polybutylene terephthalate and other polyesters, nylon, polyamides such as polyamide amine, polyvinyl acetal, polyvinyl benzyl aldehyde, polyvinyl butyral resin and other polyvinyl acetal resins, ionomer resins, polyphenylene ether, polyphenylene sulfide, polycarbonate, polyether ether ketone, polyacetal, ABS resin, LCP (liquid crystal polymer), fluororesin, polyurethane resin, silicone resin, various elastomers, or modified products of these resins.

[0215] These thermoplastic resins may be uniform in the resin phase of the heat sink, or may be phase-separated and have their shapes recognizable. In the case of phase-separated, the shape of the thermoplastic resin in the heat sink may be granular or fibrous. In the case where the shape of the thermoplastic resin is recognizable in the heat sink, there may be a case where the thermoplastic resin is recognized as an organic filler. However, in the present invention, the organic filler refers to natural materials such as wood powder, cellulose that may be modified, starch, various organic pigments, etc., and the thermoplastic resin is not included in the organic filler.

[0216] By including a thermoplastic resin or an organic filler, appropriate elongation can be imparted to the composition, the generated stress can be relaxed, and the generation of cracks in a temperature cycle test can be suppressed.

[0217] When thermoplastic resin and organic filler are insoluble in the situation of thermosetting resin, the viscosity of composition of the present invention can be prevented from rising, and when being molded as sheet-like in the following manner, the smoothness of sheet surface can be improved. In this case, by mixing thermoplastic resin and organic filler that are insoluble in thermosetting resin with a large amount of inorganic fillers simultaneously, the components that thermoplasticity and elongation become can be efficiently dispersed in the cured product, and stress is easily relaxed. Therefore, the elastic modulus of cured product can be suppressed from cracking without reducing the cured product. Based on these reasons, as thermoplastic resin, polyamide resins such as nylon, cellulose resins, etc. are preferably used, and polyamide resins such as nylon are particularly preferred.

[0218] When the thermoplastic resin observed in the heat sink as a cured product is in the form of particles, the upper limit of the average particle size is preferably 100 μm or less, more preferably 50 μm or less, and further preferably 30 μm or less. By setting the average particle size to be below the upper limit, sheet-like cured products of various thicknesses can be prepared without worrying about reduced thermal conductivity. The average particle size of the granular thermoplastic resin is determined by observing the cross section of the cured product and the average value of the longest diameters of any 20 particles.

[0219] The composition of the present invention may contain an organic solvent, for example, in order to improve coating properties when it is molded into a sheet-shaped cured product through a coating step.

[0220] Examples of the organic solvent that may be contained in the composition of the present invention include methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, butyl acetate, isobutyl acetate, propylene glycol monomethyl ether, etc. These organic solvents may be used alone or in combination of two or more.

[0221] When the composition of the present invention contains an organic solvent, its content is appropriately determined according to the operability when manufacturing the heat sink, etc. Generally, the organic solvent is preferably used in a manner such that the solid content (the total of components other than the solvent) concentration in the composition of the present invention is 10% by weight or more, especially 40% by weight or more, and 90% by weight or less, especially 80% by weight or less.

[0222] [Inorganic filler]

[0223] The composition of the present invention contains at least the BN aggregate powder of the present invention as an inorganic filler.

[0224] The composition of the present invention may contain an inorganic filler other than the BN aggregate powder of the present invention. In this case, a spherical filler is preferred as the inorganic filler other than the BN aggregate powder of the present invention.

[0225] The thermal conductivity of the spherical filler used together with the BN aggregate powder of the present invention is preferably 10 W / m·K or more, more preferably 15 W / m·K or more, and further preferably 20 W / m·K or more. The new Mohs hardness of the spherical filler used together with the BN aggregate powder of the present invention is preferably 3.1 or more, more preferably 5 or more. In particular, the spherical filler used together with the BN aggregate powder of the present invention preferably has a thermal conductivity of 20 to 30 W / m·K and a new Mohs hardness of 5 to 10. By using such a spherical filler in combination with the BN aggregate powder of the present invention, the adhesion and heat dissipation of the heat sink obtained can be improved.

[0226] Here, "spherical" only needs to be generally recognized as a sphere. For example, the case where the average circularity is 0.4 or more can be regarded as a sphere, and the case where it is 0.6 or more can be regarded as a sphere. Generally, the upper limit of the average circularity is 1. The circularity can be measured by performing image processing on its projected image. The circularity can be measured, for example, using the FPIA series of Sysmex Corporation.

[0227] The spherical filler is preferably at least one selected from the group consisting of alumina, synthetic magnesite, crystalline silica, aluminum nitride, silicon nitride, silicon carbide, zinc oxide, and magnesium oxide. By using these preferred spherical fillers, the heat dissipation of the obtained heat sink can be further improved.

[0228] The average particle size of the spherical filler is preferably within a range of 0.5 μm or more and 40 μm or less. It is believed that when the average particle size is 0.5 μm or more, the resin and filler can flow easily during heat molding, and the interfacial adhesion in the heat sink can be improved. When the average particle size is 40 μm or less, the dielectric breakdown characteristics of the heat sink can be easily maintained.

[0229] As other inorganic fillers, electrical insulating ones can be used, and at least one particle selected from the group consisting of carbon, metal carbides, metal oxides and metal nitrides can be listed. As examples of carbon, diamonds can be listed. As examples of metal carbides, silicon carbide, titanium carbide, tungsten carbide, etc. can be listed. As examples of metal oxides, magnesium oxide, aluminum oxide, silicon oxide, calcium oxide, zinc oxide, yttrium oxide, zirconium oxide, cerium oxide, ytterbium oxide, silicon aluminum oxynitride (ceramics containing silicon, aluminum, oxygen, and nitrogen) can be listed. As examples of metal nitrides, boron nitride, aluminum nitride, silicon nitride, etc. other than the BN aggregated particles of the present invention can be listed.

[0230] The shapes of other inorganic fillers are not limited, and may be particles, whiskers, fibers, plates, or aggregates thereof.

[0231] These inorganic fillers may be surface-treated with a surface treatment agent. As the surface treatment agent, a known surface treatment agent may be used.

[0232] These inorganic fillers may be used alone or in combination of two or more in any ratio.

[0233] The content of the inorganic filler in the composition of the present invention is preferably 30% by weight or more, more preferably 40% by weight or more, and further preferably 50% by weight or more in 100% by weight of the composition of the present invention excluding the solvent. In addition, the content of the inorganic filler is preferably 99% by weight or less, more preferably 90% by weight or less, and further preferably 80% by weight or less.

[0234] When the content of the inorganic filler is above the above lower limit, the effect of improving thermal conductivity and the effect of controlling the linear expansion coefficient caused by the inclusion of the inorganic filler can be fully obtained. When the content of the inorganic filler is below the above upper limit, there is a tendency to obtain the moldability of the cured product and the interface adhesion in the composite molded body described below.

[0235] When the BN aggregate powder of the present invention and a spherical filler such as alumina are used together as an inorganic filler, the content ratio of the BN aggregate powder of the present invention to the spherical filler in the composition of the present invention is not particularly limited, but is preferably 90:10 to 10:90, and preferably 80:20 to 20:80 in terms of weight ratio.

[0236] In order to effectively obtain the effect produced by using the BN aggregate powder of the present invention, it is preferred that 30% by weight or more, particularly 40% by weight or more of the inorganic filler used is the BN aggregate powder of the present invention. In the present invention, it is preferred to use only the BN aggregate powder of the present invention, or only the BN aggregate powder of the present invention and the above-mentioned spherical filler as the inorganic filler.

[0237] <Method for producing the composition of the present invention>

[0238] The composition of the present invention can be obtained by uniformly mixing the inorganic filler containing the BN aggregate powder of the present invention, the resin component such as a thermosetting resin, and other components added as needed by stirring or kneading. During mixing, for example, a common kneading device such as a mixer, a kneader, a single screw or a twin screw kneader can be used. During mixing, heating can also be performed as needed.

[0239] The order of mixing the various ingredients is also arbitrary as long as no special problems such as reaction or sedimentation occur. For example, the following method can be cited: thermosetting resin components are mixed and dissolved in an organic solvent (such as methyl ethyl ketone) to prepare a resin liquid, an inorganic filler and other ingredients are fully mixed to the obtained resin liquid and mixed, then an organic solvent for adjusting the viscosity is added and mixed, and then an additive such as a curing agent or a curing accelerator, or a dispersant is added and mixed.

[0240] [Heat sink]

[0241] A method for producing the heat dissipation sheet of the present invention by forming a sheet-shaped cured product using the composition of the present invention will be described below.

[0242] The sheet-like cured product can be produced by a commonly used method, for example, by molding and curing the composition of the present invention into a sheet-like shape.

[0243] The composition of the present invention may be formed into a sheet by a commonly used method.

[0244] For example, when the composition of the present invention has plasticity or fluidity, the composition can be formed by curing in a desired shape, for example, in a state accommodated in a mold. In this case, injection molding, injection compression molding, extrusion molding, compression molding, and vacuum compression molding can be used.

[0245] The solvent in the composition of the present invention can be removed by a known heating method such as a hot plate, a hot air oven, an IR heating oven, a vacuum dryer, or a high-frequency heater.

[0246] In addition, a sheet-shaped cured product can also be obtained by cutting the cured product of the composition of the present invention into a desired shape.

[0247] The sheet-like cured product can also be obtained by forming a slurry of the composition of the present invention (hereinafter referred to as "sheet slurry") into a sheet by a doctor blade method, a solvent casting method, an extrusion film forming method or the like.

[0248] An example of a method for producing a sheet-shaped cured product using the sheet slurry will be described below.

[0249] <Coating process>

[0250] First, a coating film is formed on the surface of a substrate using a sheet slurry.

[0251] That is, a coating film is formed on a substrate using the sheet slurry by dipping, spin coating, spraying, blade coating, or any other method. When applying the sheet slurry, a coating device such as a spin coater, a slit coater, a die coater, or a blade coater can be used. By using these devices, a coating film of a predetermined film thickness can be uniformly formed on a substrate.

[0252] As the substrate, the following copper foil and PET film are generally used, but there are no particular limitations.

[0253] <Drying process>

[0254] The coating film formed by applying the sheet slurry is dried at a temperature of usually 10 to 150°C, preferably 25 to 120°C, and more preferably 30 to 110°C in order to remove the solvent and low molecular weight components.

[0255] When the drying temperature is below the upper limit, the curing of the thermosetting resin in the slurry is suppressed, and the resin flows in the subsequent pressurization process, which tends to facilitate the removal of voids. When the drying temperature is above the lower limit, the solvent can be effectively removed.

[0256] The drying time is usually 5 minutes to 10 days, preferably 10 minutes to 3 days, more preferably 20 minutes to 1 day, and particularly preferably 30 minutes to 4 hours. When the drying time is above the lower limit, the solvent can be fully removed, and the tendency of the residual solvent to form pores in the sheet-like solidified product can be suppressed. When the drying time is below the upper limit, the productivity is improved, and the manufacturing cost can be suppressed.

[0257] <Pressing process>

[0258] It is desirable to perform a pressurization step after the drying step for the purpose of bonding the inorganic fillers to each other to form a heat channel, to eliminate voids or pores in the sheet, to improve the adhesion with the substrate, etc. In the pressurization step, it is desirable to apply 10 kgf / cm 2 The load is preferably 20 kgf / cm2 More preferably, 50 kgf / cm 2 More than, and preferably 2000kgf / cm 2 Below, more preferably 1000kgf / cm 2 , and preferably 800kgf / cm 2 By setting the load during pressurization to be below the upper limit, the secondary particles of the inorganic filler are not destroyed, and a sheet having high thermal conductivity and no pores in the sheet can be obtained. By setting the load during pressurization to be above the lower limit, the contact between the inorganic fillers becomes good, and a heat conduction path is easily formed, so a sheet having high thermal conductivity can be obtained.

[0259] In the pressurizing step, it is desirable to heat the dried film on the substrate at a temperature of 25°C or higher. The heating temperature is preferably 40°C or higher, more preferably 50°C or higher, and further preferably 60°C or higher, and preferably 300°C or lower, more preferably 250°C or lower, further preferably 200°C or lower, and particularly preferably 180°C or lower. By performing the pressurizing step in this temperature range, the melt viscosity of the resin in the coating film can be reduced, and there can be no voids or pores in the sheet. By making the heating temperature below the above upper limit, there is no worry about the decomposition of the organic component or the worry about the residual solvent becoming vapor and forming pores, which is preferred.

[0260] The time of pressurization process is usually more than 30 seconds, preferably more than 1 minute, more preferably more than 3 minutes, and then preferably more than 5 minutes, and preferably less than 4 hours, more preferably less than 2 hours, and then preferably less than 1 hour, particularly preferably less than 45 minutes.Being below the above-mentioned upper limit by pressurization time, there is the manufacturing time that can suppress sheet-like solidified material, and the tendency of production cost can be reduced.On the other hand, being above the above-mentioned lower limit by pressurization time, there is the tendency that can fully remove the hollow or pore in sheet-like solidified material, and heat transfer performance or withstand voltage characteristic can be improved.

[0261] <Curing process>

[0262] The curing step for completing the curing reaction may be performed under pressure or without pressure. In the case of pressure, it is desirable to perform the step under the same conditions as the pressure step for the same reasons as above. The pressure step and the curing step may also be performed simultaneously.

[0263] In particular, in the sheet-forming step that includes a pressurizing step and a curing step, it is preferred that the pressurizing and curing be performed while applying a load within the above range.

[0264] There is no particular limitation on the thickness of the sheet-like cured product formed in this way, i.e., the heat sink of the present invention, but it is preferably 50 μm or more, more preferably 100 μm or more, and preferably 400 μm or less, more preferably 300 μm or less. When the thickness of the heat sink is above the lower limit, there is a tendency to obtain withstand voltage characteristics and improve dielectric breakdown voltage. When the thickness of the heat sink is below the upper limit, there is a tendency to achieve miniaturization or thinning of the device, and to suppress the thermal resistance of the obtained heat sink.

[0265] [Composite molded article]

[0266] The heat sink of the present invention can be used in the form of a composite molded body in which the heat sink of the present invention and the metal part are laminated and integrated. In this case, the metal part may be provided on only one surface of the heat sink of the present invention, or on two or more surfaces. For example, the heat sink of the present invention may have a metal part only on one surface, or on both surfaces. In addition, the metal part may be patterned.

[0267] Such a composite molded body can be produced by using a metal part as the above-mentioned substrate and forming a sheet-like article including the composition of the present invention on the substrate according to the above-mentioned method.

[0268] Alternatively, the composite molded body can be produced by peeling a sheet-like object formed on a base material different from the metal portion from the base material and then heat-compressing and bonding the sheet-like object to a metal member serving as the metal portion.

[0269] In this case, a sheet-like article comprising the composition of the present invention is formed in the same manner as above except that the coating is performed on a substrate such as PET which can be treated with a release agent. Thereafter, the sheet-like article is peeled off from the substrate and placed on another metal plate or integrated by applying pressure while sandwiched between two metal plates.

[0270] As the metal plate, a metal plate with a thickness of about 10 to 10000 μm including a copper-plated, aluminum-plated, nickel-plated metal, etc. can be used. In addition, the surface of the metal plate can be physically roughened or chemically treated with a surface treatment agent, etc. From the perspective of the close adhesion between the resin composition and the metal plate, it is more preferred to have been treated with these treatments.

[0271] [Semiconductor devices]

[0272] The semiconductor device of the present invention is equipped with the heat sink of the present invention as a heat dissipation substrate, and can achieve high power and high density on the basis of high reliability through the heat dissipation effect and voltage resistance characteristics generated by its high thermal conductivity. In the semiconductor device, components other than the heat sink of the present invention such as aluminum wiring, sealing material, packaging material, heat sink, heat dissipation paste, solder, etc. can appropriately adopt conventionally known components.

[0273] Example

[0274] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to the following Examples unless it exceeds the gist of the present invention.

[0275] The values ​​of various conditions or evaluation results in the following examples are the same as the preferred ranges in the embodiments of the present invention, and represent the preferred range of the present invention. The preferred range of the present invention can be determined by considering the range represented by the combination of the preferred range in the above-mentioned embodiment and the values ​​of the following examples or the values ​​of the examples.

[0276] [Measurement conditions]

[0277] Various characteristics or properties in the following examples and comparative examples were measured by the methods described below.

[0278] <The volume average particle size of BN aggregate powder (D 50 )>

[0279] The D of BN aggregate powder was measured using the "Morphologi" manufactured by Malvern. 50 (μm).

[0280] <Tap density of BN aggregate powder>

[0281] The heated and calcined sample was subjected to wind classification to prepare a powder sample with a volume average particle size of less than 100 μm. The sample was placed in a 10 ml graduated cylinder and manually tapped until the sample volume became fixed, and the tap density was calculated by dividing the weight of the sample by the volume after tapping. The above method was performed according to JIS R1628 except that a 10 ml graduated cylinder was used.

[0282] <Interstitial volume of BN aggregate powder particles, intra-particle porosity of BN aggregate particles>

[0283] It is determined by mercury intrusion measurement using a mercury porosimeter. Using AutoPore IV manufactured by Micromeritics, the sample is subjected to a 10-minute decompression treatment under reduced pressure (less than 50 μmHg), and the powder density and total pore volume are determined. In addition, the mercury intrusion exit curve is measured. Assuming that the pores are cylindrical, the pore volume of the region with a pore diameter of 2.0 μm or more (divided particle size) is calculated as the intergranular interstitial volume.

[0284] The intra-particle pore volume was determined by subtracting the inter-particle volume from the total pore volume, and the ratio of the intra-particle pore volume to the volume of the powder (1 / powder density) was defined as the intra-particle porosity.

[0285] The mercury intrusion measurement was performed according to JIS R1655, and the surface tension of BN was set to 485 dyn / cm 2 , the contact angle was set to 140°, and the measurement temperature was set to 23-26°C.

[0286] <Compression failure strength of BN aggregate powder>

[0287] The test was conducted using a Shimadzu micro compression tester MCT-510 manufactured by Shimadzu Corporation at room temperature (20-30°C) with a test force of 98 mN, a load speed of 4.84 mN / sec, and a flat φ100 μm upper pressure head. One BN aggregate particle with a particle size of about 50 μm was screened for the test, and this step was performed 5 times, and the compression failure strength was calculated using the average value of the 5 times. The failure strength was calculated using the following formula.

[0288] Cs=2.48 / πd 2

[0289] Cs: Compression strength (MPa)

[0290] P: Destructive test force (N)

[0291] d: particle size (mm)

[0292] <Thermal conductivity in the thickness direction of sheet-shaped molded body>

[0293] Regarding the thermal conductivity of the heat sink, the thermal resistance values ​​of four sheets of different thicknesses were measured using the following apparatus and conditions, and the thermal conductivity was measured by a conventional method (according to ASTM D5470) based on the slope of the thermal resistance value relative to the sheet thickness.

[0294] (1) Thickness: Thickness (μm) when the pressing pressure is set to 3400 kPa when using T3Ster-DynTIM manufactured by Mentor Graphics

[0295] (2) Measurement area: The area of ​​the portion that transfers heat when using T3Ster-DynTIM manufactured by Mentor Graphics (cm 2 )

[0296] (3) Thermal resistance: Thermal resistance when pressing with a pressure of 3400 kPa using T3Ster-DynTIM manufactured by Mentor Graphics (K / W)

[0297] (4) Thermal conductivity: The thermal resistance values ​​of four sheets having different thicknesses were measured, and the thermal conductivity (W / m·K) was calculated according to the following formula.

[0298] Formula: Thermal conductivity (W / m·K) = 1 / ((slope (thermal resistance value / thickness): K / (W·μm))×(area: cm 2 ))×10 -2

[0299] <Dielectric Withstand Characteristics of Sheet Molded Article>

[0300] The voltage of a sheet-like molded product having a thickness of 150 μm was increased by 500 V every 1 minute in insulating oil, and the voltage at which the sample was destroyed was determined.

[0301] [Preparation and evaluation of BN aggregate powder from BN slurry]

[0302] The BN aggregate particles used in the following Examples and Comparative Examples were produced and evaluated by the following methods.

[0303] <Preparation of BN slurry>

[0304] (raw material)

[0305] The raw material h-BN powder (the half value width of the (002) peak measured by powder X-ray diffraction is 2θ = 0.67°, the total oxygen concentration is 7.5% by weight, and the specific surface area is 116 m 2 / g, and the total pore volume is 0.754cm 3 / g): 10000g

[0306] Binder ("Takiselam M160L" manufactured by Taki Chemical Co., Ltd., solid content concentration 21% by weight): 11496 g

[0307] Surfactant (surfactant "Ammonium lauryl sulfate" manufactured by Kao Corporation, solid content concentration 14% by weight): 250 g

[0308] (Preparation of slurry)

[0309] A predetermined amount of raw material h-BN powder was weighed and placed in a resin bottle, and then a predetermined amount of binder was added. Then, a predetermined amount of surfactant was added, and then zirconia ceramic beads were added, and stirred for 1 hour on a pot mill rotary table to prepare a slurry.

[0310] <Granulation>

[0311] The granulation using the BN slurry was carried out using a spray dryer P260 manufactured by PRECI Co., Ltd. under the conditions of a disk rotation speed of 15,000 to 20,000 rpm and a drying temperature of 85°C.

[0312] <Production of BN Aggregate Particles>

[0313] The BN granulated powder was placed in a graphite crucible with a lid, and the temperature was raised to 2000°C at 63°C / hour while introducing nitrogen, and after reaching 2000°C, the temperature was maintained for 5 hours while introducing nitrogen, and then cooled to room temperature to obtain a heat-treated sample.

[0314] The heated sample in the graphite crucible was divided and sorted out by taking the outer part 1 cm from the inner wall surface side (upper layer, side peripheral layer, lower layer) of the graphite crucible as sample (A), taking the inner part 1 cm from the sample (A) as sample (B), and taking the inner part 1 cm from the sample (B) as sample (C). Sample (C) was the inner part 2 cm from the inner wall surface side (upper layer, side peripheral layer, lower layer) of the graphite crucible.

[0315] <Classification>

[0316] The BN aggregate powders separated and heated were subjected to air classification using AC-15 manufactured by Nisshin Engineering Inc. The divided samples (A), (B), and (C) were classified into particles smaller than 100 μm and particles larger than 100 μm.

[0317] <Evaluation>

[0318] After classification, the tap density, interparticle volume, intraparticle porosity and compressive strength of particles less than 100 μm were measured according to the above method. In addition, the average particle size was measured. The divided samples (A), (B), and (C) were designated as sample Nos. (A)-1 to (A)-2, (B)-1, and (C)-1 to (C)-5, respectively, and the measurement results are shown in Table 1.

[0319] [Table 1]

[0320]

[0321] It is to be noted that, through SEM observation, it was confirmed that all of the BN aggregate powders of Sample Nos. (A)-1 to (A)-2, (B)-1, and (C)-1 to (C)-5 had a paper house-like structure.

[0322] [Production and evaluation of sheet-shaped molded products]

[0323] In the following examples and comparative examples, the BN aggregate powders (A)-1 to (A)-2, (B)-1, and (C)-1 to (C)-5 obtained above were used as inorganic fillers, and resin compositions containing BN aggregate powders were prepared by the following method to produce sheet-like molded bodies.

[0324] <Preparation of resin composition containing BN aggregate powder>

[0325] The raw materials used are as follows.

[0326] <Thermosetting resin component>

[0327] Resin component 1: a resin having structure (2) (R 3 = Structure (4)) and Structure (3) (R 4 , R 5 , R 6 , R 7 = methyl) specific epoxy resin

[0328] Weight average molecular weight based on polystyrene: 30,000

[0329] Epoxy equivalent: 9000g / equivalent

[0330] Resin component 2: Bisphenol F solid epoxy resin manufactured by Mitsubishi Chemical Co., Ltd. Weight average molecular weight in terms of polystyrene: 60,000

[0331] Resin component 3: Bisphenol A type liquid epoxy resin manufactured by Mitsubishi Chemical

[0332] Resin component 4: a multifunctional epoxy resin having a structure having four or more glycidyl groups per molecule manufactured by Nagase ChemteX

[0333] Resin component 5: Hydrogenated bisphenol A type liquid epoxy resin manufactured by Mitsubishi Chemical Co., Ltd. Resin component 6: p-aminophenol type liquid epoxy resin manufactured by Mitsubishi Chemical Co., Ltd.

[0334] <Curing agent ingredients>

[0335] Curing agent 1: "MEH-8000H" manufactured by Meiwa Chemicals Co., Ltd.

[0336] Phenolic resin curing agent

[0337] <Curing catalyst component>

[0338] Curing catalyst 1: "2E4MZ-A" manufactured by Shikoku Chemical Co., Ltd.

[0339] 2,4-Diamino-6-[2'-ethyl-4'-methylimidazolyl-(17')]-ethyl-s-triazine

[0340] (Compound containing a nitrogen atom and having a triazine ring as a heterocyclic structure)

[0341] Molecular weight: 247

[0342] Curing catalyst 2: "C11Z-CN" manufactured by Shikoku Chemical Co., Ltd.

[0343] 1-Cyanoethyl-2-undecylimidazole

[0344] Molecular weight: 275

[0345] <Inorganic filler ingredients>

[0346] Inorganic filler 1: BN aggregate powder (C)-1 to (C)-5

[0347] Inorganic filler 2: BN aggregate powder (B)-1

[0348] Inorganic filler 3: BN aggregate powder (A)-1 to (A)-2

[0349] Inorganic filler 4: Spherical alumina particles manufactured by Admatechs

[0350] New Mohs hardness: 9

[0351] Volume average particle size: 6.5 μm

[0352] Thermal conductivity: 20~30W / m·K

[0353] <Example 1>

[0354] A mixture was prepared using a rotation-revolution stirring device to obtain resin component 1: 7.02 weight %, resin component 3: 7.02 weight %, resin component 4: 6.67 weight %, curing agent 1: 7.37 weight %, curing catalyst 1: 0.42 weight %, inorganic filler 1: 51.14 weight %, and inorganic filler 4: 20.35 weight %. In addition, when preparing the above mixture, 18.6 weight % of methyl ethyl ketone and cyclohexanone were used respectively so that the above mixture became 62.8 weight % (solid content concentration) in the coating slurry.

[0355] The obtained coating slurry (sheet slurry) was applied onto a PET substrate by a doctor blade method, dried by heating at 60°C for 120 minutes, and then heated at 42°C and 1500 kgf / cm 2 The pressing was performed for 10 minutes to obtain a sheet-like molded product having a thickness of 150 μm. The total content of methyl ethyl ketone and cyclohexanone in the sheet-like molded product was 1% by weight or less.

[0356] The thermal conductivity and withstand voltage characteristics of the obtained sheet-like molded body were measured. Table 2 shows the results.

[0357] <Examples 2 to 6, Comparative Examples 1 and 2>

[0358] According to the method of Example 1, sheet-like molded products were prepared with the compositions shown in Table 2, and the evaluations were performed.

[0359] [Table 2]

[0360]

[0361] As shown in Table 2, by using the BN aggregate powder of the present invention having a tap density and a particle gap volume within a specific range, a heat sink having excellent thermal conductivity and withstand voltage characteristics can be realized.

[0362] While the present invention has been described in detail using specific embodiments, it will be apparent to one skilled in the art that various modifications can be made without departing from the spirit and scope of the present invention.

[0363] This application is based on Japanese Patent Application No. 2019-034518 filed on February 27, 2019, the entirety of which is incorporated herein by reference.

Claims

1. A boron nitride aggregate powder having a tap density of 0.65 g / ml or more and 0.78 g / ml or less and a particle interstitial volume of 0.5 ml / g or more, The boron nitride aggregated powder includes BN aggregated particles having an intra-particle porosity of 45% or more and 60% or less.

2. The boron nitride aggregate powder according to claim 1, wherein: The interstitial volume of the particles is less than 0.9 ml / g.

3. The boron nitride aggregate powder according to claim 1 or 2, wherein: The boron nitride aggregate powder has an average particle size of 20 μm or more and 200 μm or less.

4. The boron nitride aggregate powder according to claim 1 or 2, wherein: The interstitial volume of the particles is greater than or equal to 0.58 ml / g and less than or equal to 0.8 ml / g.

5. The boron nitride aggregate powder according to claim 1 or 2, wherein: The boron nitride aggregated powder is a paper house-like structure. 6 . A heat sink comprising the boron nitride aggregated powder according to claim 1 .

7. A semiconductor device using the heat sink according to claim 6.

Citation Information

Patent Citations

  • Control method of engine provided with supercharger

    JP1991260327A

  • Polyether polyol resin, hardenable resin composition and hardened product thereof

    JP2006176658A

  • Hexagonal boron nitride powder and method for producing the same

    JP2011098882A

  • Epoxy resin composition, epoxy resin sheet and metal base circuit board using the same

    JP2017082091A

  • Address book display system, electronic apparatus, address book display program

    JP2019034518A